Sharia and Politics in The Context of Globalization and Society 5.0 - Masykuri Abdillah (Universitas Islam Negeri Jakarta, 2022)
This article aims to describe and analyze globalization and its impact on Islamic politics and Islamic law (sharia) in the modern era. Globalization has brought about a new set of ethics and norms in human relations which in some ways have led to changes in worldviews as well as social, economic, and political systems in the world. Most Muslim scholars accept it, including the influence of Western civilization, with certain adjustments that refer to Islamic teachings and national identity. In most Muslim countries, globalization has affected changes in state systems, such as nation-state, democracy, and protection of human rights. In addition, globalization has affected the status of Islamic law, especially in the form of secularization of national law, although this was later revised with efforts of Islamization of national law. Globalization also has an impact on the need to reinterpret several provisions of Islamic law that are not in line with modern perspectives and challenges, especially provisions related to society 5.0, such as legitimizing digital transactions, peaceful relations between Muslims and non-Muslims, and the understanding of defensive jihad.Keywords: globalization; Islamic politics; Islamic law AbstrakArtikel ini bertujuan untuk mendeskripsikan dan menganalisis globalisasi dan dampaknya terhadap politik Islam dan hukum Islam (syariah) di era modern. Globalisasi telah membawa seperangkat etika dan norma baru dalam hubungan manusia yang dalam beberapa hal menyebabkan perubahan pandangan dunia serta sistem sosial, ekonomi, dan politik di dunia. Sebagian besar ulama dan intelektual Muslim menerimanya, termasuk pengaruh peradaban Barat, dengan penyesuaian tertentu yang mengacu pada ajaran Islam dan identitas bangsa. Di sebagian besar negara Muslim, globalisasi telah mempengaruhi perubahan sistem negara, seperti nation-state, demokrasi, dan perlindungan hak asasi manusia. Selain itu, globalisasi telah mempengaruhi status hukum Islam, terutama dalam bentuk sekularisasi hukum nasional, meskipun kemudian direvisi dengan upaya Islamisasi hukum nasional. Globalisasi juga berdampak pada kebutuhan untuk menafsirkan kembali beberapa ketentuan hukum Islam yang tidak sejalan dengan perspektif dan tantangan modern, terutama ketentuan yang terkait dengan masyarakat 5.0, seperti legitimasi transaksi digital, hubungan damai antara Muslim dan non- Muslim, dan pemahaman tentang jihad defensif.Kata Kunci: globalisasi; politik Islam; hukum Islam